Analysis of the Performance of Islamic Commercial Banks in Indonesia Using the Islamicity Performance Index Approach for the 2014-2016 periods - Sadly, Effendy (Universitas Malikussaleh, 2021)
This study aims to reveal the application of Islamic principles to the performance of Islamic Commercial Banks in Indonesia for the 2014 to 2016 period using the Islamicity Performance Index approach. The ratios in the Islamiciti Performance Index are Profit Sharing Ratio, Zakat Performance Ratio, Equitable Distribution Ratio, Directors-employee Wefare Ratio, Islamic Income vs Non-Islamic Income. The data used in this study are secondary data. The population of this research is all Islamic commercial banks in Indonesia from 2014 to 2016 with a sample of two banks, namely Bank Muamalat Indonesia and Bank Syariah Mandiri. Sampling was done using purposive sampling method. The results showed that the performance of Islamic Commercial Banks in Indonesia using the Islamicity Performance Index approach for the period 2014 to 2016 has the predicate